Impact of polyvascular disease and renal dysfunction on cardiovascular outcomes in diabetes: post hoc analyses from EMPA-REG OUTCOME. (25th November 2020) - Verma, S; Mazer, C.D; Inzucchi, S.E; Wanner, C; Ofstad, A.P; Johansen, O.E; Zwiener, I; George, J.T; Butler, J; Zinman, B
Abstract: Background: Individuals with polyvascular disease and impaired renal function are at high risk of cardiovascular (CV) events, but this relationship is not well investigated in people with type 2 diabetes (T2D). Furthermore, the impact of polyvascular disease plus renal dysfunction on the risk for hospitalisation for heart failure (HHF) remains unclear. Purpose: We investigated this in a post hoc analysis of the EMPA-REG OUTCOME trial in which empagliflozin reduced risk of CV death and HHF versus placebo in people with T2D and vascular disease. In addition, we explored the treatment effect of empagliflozin on CV, HF and mortality outcomes across the spectrum of baseline polyvascular disease and impaired renal function. Methods: Patients with T2D, CV disease and estimated glomerular filtration rate (eGFR) of ≥30 ml/min/1.73 m 2 received empagliflozin 10 mg, 25 mg, or placebo. Vascular beds (VBs) were defined as coronary artery disease, peripheral artery disease, and cerebrovascular disease (Fig). By use of Cox regression, we explored the association between baseline eGFR < or ≥60 ml/min/1.73 m 2, with or without polyvascular disease (1 vs ≥2 VBs involved), and CV death, HHF, CV death (excl. fatal stroke)/HHF, and all-cause mortality (ACM), as well as the treatment effect of empagliflozin versus placebo on these outcomes. Results: Patients with ≥2 VBs involved and eGFR <60 ml/min/1.73 m 2 [n=463], were slightly older (mean age 68.2 vs. 64.3 or 62.6 years), had T2D duration >10 years more often (73.4% vs. 63.2% or 54.9%), and a higher HF prevalence at baseline (19.4% vs. 11.1% or 9.2%) versus those with ≥2 VBs involved and eGFR ≥60 ml/min/1.73 m 2 [n=866], or those with only 1 VB involved regardless of eGFR [n=5630], respectively. However, characteristics were generally balanced between treatment groups. Notably, co-existing polyvascular disease and eGFR <60 ml/min/1.73 m 2 was strongly associated with increased risk of all outcomes. The placebo incidence rates per 1000 patient-years for CV death were 14.4 (95% CI 10.9, 18.3) and 19.6 (12.8, 27.8) in those with 1 VB involved and eGFR ≥60 or eGFR <60, respectively, and 32.7 (21.7, 45.8), and 52.4 (32.9, 76.5) in those with 2 VBs and eGFR ≥60 or eGFR <60 ml/min/1.73 m 2, respectively. Importantly, empagliflozin reduced the risk for all outcomes regardless of number of VBs affected and kidney function (Fig). Conclusions: Co-existing polyvascular disease and eGFR <60 ml/min/1.73 m 2 confer an extremely high risk of CV and all-cause mortality, and HHF. Empagliflozin lowered this risk consistently compared with placebo, regardless of polyvascular disease and impaired kidney function. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Boehringer Ingelheim and Eli Lilly and Company Diabetes Alliance